Decreased Sialic Acid Content of Plasma von Willebrand Factor in Precapillary Pulmonary Hypertension - Lopes, Antonio Augusto; de Souza, Bruno Ferraz; Maeda, Nair Yukie (Thrombosis and Haemostasis, 2000)
In pulmonary hypertension, defective von Willebrand factor protein (vWF) lacking large multimers is present in circulation. This is associated with evidence of chronic endogenous platelet activation. Since asialo vWF has been shown to promote platelet activation and aggregation, we decided to investigate possible changes in the sialic acid content of plasma vWF in patients with precapillary pulmonary hypertension. vWF-associated sialic acid was measured indirectly as a wheat germ agglutinin-reactive substance (WGA-RS, Western blotting), and directly, as a thiobarbituric acid-reactive substance (TBA-RS, spectrophotometric reading). In the sixteen patients we studied (ages 8–45 yr), circulating vWF concentration was 2.18 times normal (p <0.001). However, patient vWF subunit contained 19% (WGA-RS) to 24% (TBA-RS) less sialic acid than the normal protein (p <0.05 for both determinations). In five patients, vWF-associated sialic acid was below 50% normal. We conclude that circulating vWF is hyposialylated in precapillary pulmonary hypertension and speculate that this might influence its interaction with platelets in vivo in these patients.
Keywords: Sialic acid; von Willebrand factor; pulmonary hypertension